Multiplex Assay of Second-Line Anti-Tuberculosis Drugs in Dried Blood Spots Using Ultra-Performance Liquid Chromatography-Tandem Mass Spectrometry - Lee, Kyunghoon (Ann Lab Med, 2016)
As dried blood spots (DBSs) have various advantages over conventional venous blood sampling, some assays for detection of one or two anti-tuberculosis (TB) drugs in DBSs have been developed. However, there are no assays currently available for the simultaneous measurement of three or more anti-TB drugs in DBSs. In this study, we developed and evaluated a multiplex method for detecting nine anti-TB drugs including streptomycin, kanamycin, clarithromycin, cycloserine, moxifloxacin, levofloxacin, para-aminosalicylic acid, prothionamide, and linezolid in DBSs by using ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). Seventy-nine patient samples of DBS were analyzed on the UPLC-MS/MS system. All drug concentrations were determined within 4 min, and assay performance was evaluated. All drugs were clearly separated without ion suppression. Within-run and between-run precisions were 1.7-13.0% and 5.7-17.0%, respectively, at concentrations representing low and high levels for the nine drugs. Lower limits of detection and quantification were 0.06-0.6 and 0.5-5.0 µg/mL, respectively. Linearity was acceptable at five level concentrations for each drug. Correlations between drug concentrations in plasma and DBSs by using Passing-Bablock regression and Pearson's rho (ρ, 0.798-0.989) were acceptable. In conclusion, we developed a multiplex assay to measure nine second-line anti-TB drugs in DBSs successfully. This assay provided convenient and rapid drug quantification and could have applications in drug monitoring during treatment.